Standards are good (for) business: standardised comparison and the private sector in education
The article examines how and why the method of comparison against standards has benefited non-state actors and businesses in the education sector. Drawing on brief examples from international standard schools in Qatar, Indonesia and Mongolia, the author examines how the global education industry uses the reference to ‘international standards’ as a selling point to roll out their own school reform package. un argument de vente pour déployer leur propre paquet de réformes scolaires

(untitled) - Steiner-Khamsi, Gita (Globalisation, Societies and Education, 2016)
Keywords: Education industry; Globalisation; Methods of comparison; Policy borrowing and lending; Policy studies; Standards